Bilinear load-deflection model of fiber-reinforced polymer–concrete composite beam with interface slip. (10th July 2015) - Wang, Jingquan; Zou, Xingxing; Feng, Yu
The design of fiber-reinforced polymer–concrete hybrid beam is usually governed by deformation. Due to the rigidity degradation caused by fiber-reinforced polymer–concrete slip, the load–slip and load–deflection curves demonstrate a bilinear characteristic. The originality of this article is to propose a bilinear analytical model and to determine two dominant parameters in this model, namely, initial bond stress and slip modulus of the interconnection. This model consists of two distinct linear stages. In Stage I, full composite action between fiber-reinforced polymer and concrete is obtained, and no slip exists; Stage II commences once interfacial bond force diminishes, when slip increases linearly versus load, and the overall beam rigidity drops compared with that in Stage I, indicating only partial composite action is realized. Finally, three large-scale specimens were tested to validate the proposed bilinear model and to calculate the two parameters.